Penerapan Smart Governance Melalui Aplikasi Siganteng di Perumda Tirta Benteng Kota Tangerang - Hilwa, Siti; Sundari, Wiga; Almira, Dilla; nugraha, andra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Digitalization allows people to process and access information services with others. The existence of policies can support the implementation of Smart Governance because digital progress helps people utilize public services digitally, such as that done by PDAM Kota Tangerang by using the Siganteng application. This study uses a qualitative method that uses observation and interviews to collect data on how new technology can improve the quality of web-based public services at Perumda Tirta Benteng Kota Tangerang. The target informants are the community and also the public relations staff of the call center at Perumda Tirta Benteng Kota Tangerang. The results of the study show that the Siganteng application is an innovative service because it makes online complaints easier.